Late diagnosis of Wilson's disease in a case without onset of symptoms - Hefter, Harald; Weiss, P.; Wesch, Horst; Stremmel, W.; Feist, Dietrich; Freund, H. J. (Acta neurologica Scandinavica, 1995)
Wilson's disease (WD) was diagnosed on the basis of a liver biopsy, blood investigations and a radio copper test in a 60-year-old, neurologically normal female with uncharacteristic gastrointestinal complaints. Since this patient never developed symptoms indicative for WD this case suggests the possibility of a subclinical course of untreated WD.